A friendly online C compiler to improve programming skills based on student self‐assessment. Issue 6 (18th May 2015) - Cedazo, Raquel; Garcia Cena, Cecilia E.; Al‐Hadithi, Basil Mohammed
ABSTRACT This paper presents an online C compiler designed so that students can program their practical assignments in Programming courses. What is really innovative is the self‐assessment of the exercises based on black‐box tests and train students' skill to test software. Moreover, this tool lets instructors, not only proposing and classifying practical exercises, but also evaluating automatically the efforts dedicated and the results obtained by the students. The system has been applied to the 1st‐year students at the Industrial Engineering specialization at the Universidad Politecnica de Madrid. Results show that the students obtained better academic performance, reducing the failure rate in the practical exam considerably with respect to previous years, in addition that an anonymous survey proved that students are satisfied with the system because they get instant feedback about their programs. © 2015 Wiley Periodicals, Inc. Comput Appl Eng Educ 23:887–896, 2015; View this article online at wileyonlinelibrary.com/journal/cae; DOI 10.1002/cae.21660.